Teknik Budidaya Iler (Coleus atropurpureus. L. Benth) sebagai Herba untuk Penanganan Gejala (Demam dan Batuk) Penyintas Covid-19 - Muhammad Helmy Abdillah; Mila Lukmana; Herry Iswahyudi; Linda Rahmawati; Zuliyan Agus Nur Muchlis Majid; Dewi Amelia Widiyastuti; Supian Supian; Niana Zakiah; Akhmad Ramadhani; Isna Fazriah (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2022)
Iler or jewer kotok is known as an ornamental plant because it has an attractive color and shape, but the research reported that the Iler extracts have secondary metabolite compounds that are beneficial for health recovery, especially relieving wounds, fever, and coughs. In addition, Iler extract can also be an organic insecticide for horticultural crops. The reported of Iler should be cultivated in the yard or agricultural land as an insert between the main crops. The purpose of this activity is to disseminate the benefits, propagation techniques, and processing of Iler into herbs to the symptoms of COVID-19 with the agricultural extension. The results of the benefit extension activities, propagation techniques, and processing of Iler parts for herbs were an understanding and increased knowledge about the benefits of leaf, cultivation techniques, and the stages of young stems for herbs.